A literatura infantil pelo olhar da criança - Maria Elisa de Araujo Grossi (2018)
The focus of this research is to analyze childrens reception of literary books categorized as Highly Recommended for Children according to a Brazilian entity whose role is to analyze and select books for children and adolescents, the Childrens and Juvenile Book National Foundation Fundação Nacional do Livro Infantil e Juvenil - in 2015. The research involved children belonging to the 1st Cycle of Human Formation at a public elementary school, which is responsible for the systematization of literacy. The investigation was conducted at a school named Centro Pedagógico da UFMG from September 2016 to June 2017 - lasting for 9 months. Some issues are fundamental to the investigation: which criteria children use to choose a book to read? Which book elements attract childrens attention? During the reading process of the books chosen by the children in groups, which issues would they raise concerning the visual and verbal aspects of the text? To collect the data, we divided 25 children in 6 groups composed of four or five children each. We developed literary conversations based on the assumptions of academically recognized dynamics, such as the Reading Circle. A reading circle is essentially the organized sharing of a book content inside a reading community constituted for that purpose (COSSON, 2014, p. 158). We embraced the Dime (Tell me) (CHAMBERS, 2007) focus for the research methodology, stimulating children to dialogue with the books and incentivizing ideas exchange and the sharing of impressions about the text read in groups. In addition to the moments of shared reading in the six groups, we also conducted individual interviews with the children aiming at knowing their social experiences with reading. The research involved several interlocutors to better comprehend the complexity of literary reading in infancy. Therefore, we developed a dialogue with several actors that discuss childrens literature with a critical, conceptual and historical perspective (MEIRELES, 1979; CUNHA, 1986; PERROTTI, 1984, 1986; COELHO, 2000; ZILBERMAN, 2003; CADEMARTORI, 2009, 2010; LAJOLO & ZILBERMAN, 2007; HUNT, 2010; ARROYO, 2011; BAJOUR, 2012, COLOMER, 2003, 2017), with theorists of Childrens Sociology(QVORTRUP, 1993; SARMENTO, 2005; KRAMER, 2011; CORSARO, 2011), and with authors that discuss the singularities of childrens thoughts and other concepts, such as imagination and mediation (HELD, 1980; VIGOTSKI, 2007, 2008, 2009). Through the interconnections between those different studies, we intended to develop more proximity to this complex object